Comparative Study of Clinacanthus nutans Gel and Povidone Iodine Mouthwash in The Reduction of Salivary Total Bacteria and Mutans Streptococci - Rattanathongkom, Ariya; Priprem, Aroonsri; Chatchiwiwatana, Supaporn; Boonlert, Thitiworada; Hengtrakul, Panmile; Nimaeh, Nisophia (Khon Kaen University Dental Journal, 2023)
Clinacanthus nutans (C. nutans) is one of the herbal plants which has been developed into a gel for reducing inflammation in oral cavity. This study intended to compare the effect of C. nutans gel on salivary total bacterial and mutans streptococci, one of the common pathogens in oral cavity, using a solution of povidone iodine mouthwash as the standard treatment. Each volunteer (n=30), participated in a cross-over design study, received C. nutans gel and povidone iodine mouthwash with a 2-week washout. Saliva and plaque swab from the oral cavity of each volunteer were sampled at initial, followed by 30 minutes and 2 hours after each treatment, incubated for 24 and 48 hours. Comparisons between C. nutans gel, applied onto the tooth surface, and povidone iodine mouthwash, rinsed throughout the oral cavity, indicated that povidone iodine mouthwash was significantly reduced salivary total bacteria better than C. nutans gel at 30 minutes after treatment (p=0.003), but insignificance after 2 hours (p=0.740). The average colony counts of mutans streptococci from plaque samples were insignificantly reduced after 30 minutes and 2 hours-treatment by C. nutans gel or povidone iodine mouthwash (p=0.439 and p=0.076, respectively). The smell and color of C. nutans gel obtained higher satisfaction scores than those of povidone iodine mouthwash (p<0.05). Although higher satisfaction in the taste of C. nutans gel than that of the mouthwash was obtained, this difference was insignificant (p>0.05). The sensation of cleanliness after use was expectedly significantly higher with povidone iodine mouthwash (p<0.05). In conclusion, C. nutans gel may be an alternative to control the growth of bacteria in the oral cavity.